Optimization of Toolpath Planning and CNC Machine Performance in Time-Efficient Machining - Arbnor Pajaziti; Orlat Tafilaj; Afrim Gjelaj; Besart Berisha (Machines)
This study explores the optimization of the machining time in CNC milling machines by varying the machine parameters and toolpath strategies. Using the ICAM3D simulation software version 3.1.0, this approach focuses on minimizing the machining time while adhering to operational constraints. In addition, a novel approach to the optimization of the G-code in time machining, focusing on reducing the machining time while maintaining the required precision and quality of the finished product, is presented. We propose a method that integrates advanced algorithms to identify and eliminate redundant movements, optimize the toolpaths, and improve the machining strategies. The experimental results demonstrate a significant reduction in the machining time without compromising the machining accuracy, offering substantial cost savings and efficiency improvements for industrial applications. The importance of this work lies in the correct choice of the toolpath strategy. In the P3 project, the optimization process reduced the machining time from 15 min and 23 s to 13 min and 33 s by utilizing the optimized G-code. The initial machining time of 20 min and 2 s corresponds to the completion of the P3 project when the CNC machine was operated at 75% speed. To further enhance efficiency, additional software tools such as ARTCAM and ASPIRE have been utilized to implement a new toolpath strategy.